Co-follower metric on academic-social media ResearchGate: similarities between Derek de Solla Price Memorial Medal winners - Grácio, Maria Cláudia Cabrini [UNESP]; Delbianco, Natalia Rodrigues [UNESP]; Rosas, Fábio Sampaio [UNESP]; Perianes-Rodríguez, Antonio (My University, 2023)
From the perspective of the ResearchGate community, the study examines what are the relationships among researchers described by the co-followers metric. The study used the ResearchGate accounts of 18 Solla Price medalists. From each researcher's account, the following indicators were retrieved: number of readings, number of recommendations, number of research items, number of followers, list of specialties, and the comprehensive list of followers' names. Pearson's correlation coefficients were calculated between number of followers and the other three indicators. Subsequently, a symmetric matrix was built with the number of common followers among the researchers, and then normalized by Salton's Cosine. Ucinet Software was employed to construct the relationship network among the Solla Price Medal winners with the MDS layout being adopted further for visualizing the proximity between them. The study found that the number of followers is a legitimate metric of academic reputation and impact on ResearchGate. The majority of followers of the analyzed Solla Price Medalists seem to choose to follow these researchers not because of their Solla Price Medal, but because of followers' familiarity with the researchers' scientific work and publications prior to joining ResearchGate. In addition, the clusters of medalists, according to their common followers, indicate that the groupings are strongly due to co-authorship in high-impact publications between the medalist researchers as well as their different specialties and the journals used to disseminate the results of their research projects. It is concluded that, instead of social proximities, the co-follower relational metric objectively represents theoretical-methodological proximities between researchers, as perceived by the ResearchGate community, providing a clear image of the role played by the researchers analyzed in this environment.
Keywords: Academic social media metrics; Altmetrics; Author-level metrics; Follower-based relational indicator; ResearchGate